Non-thermal plasma technology for the development of antimicrobial surfaces: a review. (15th April 2016) - Nikiforov, Anton; Deng, Xiaolong; Xiong, Qing; Cvelbar, U; DeGeyter, N; Morent, R; Leys, Christophe
Abstract: Antimicrobial coatings are in high demand in many fields including the biomaterials and healthcare sectors. Within recent progress in nanoscience and engineering at the nanoscale, preparation of nanocomposite films containing metal nanoparticles (such as silver nanoparticles, copper nanoparticles, zinc oxide nanoparticles) is becoming an important step in manufacturing biomaterials with high antimicrobial activity. Controlled release of antibiotic agents and eliminating free nanoparticles are of equal importance for engineering antimicrobial nanocomposite materials. Compared to traditional chemical 'wet' methods, plasma deposition and plasma polymerization are promising approaches for the fabrication of nanocomposite films with the advantages of gas phase dry processes, effective use of chemicals and applicability to various substrates. In this article, we present a short overview of state-of-the-art engineering of antimicrobial materials based on the use of non-thermal plasmas at low and atmospheric pressure.